Use of Groin Neurectomies for Noniatrogenic Testicular and Groin Pain - Sachdeva, Sanchit; Chhabra, Avneesh; Reisch, Joan; Rozen, Shai M. (Journal of Reconstructive Microsurgery Open, 2021)
Background Chronic groin neuralgia is a life-debilitating condition that plagues patients worldwide. While groin neuralgia is usually traced to iatrogenic causes (inguinal hernia repairs, vasectomy, and hysterectomy), there is a unique subset of patients that present with noniatrogenic groin neuralgia. The diagnosis and treatment of these patients present a particular challenge.Methods A total of 30 patients (current mean age, 46.5 [range: 19–72] years) who presented with noniatrogenic groin neuralgia and received neurectomies on the iliohypogastric, ilioinguinal, and genitofemoral nerves between 2008 and 2017 were identified. A retrospective review of preoperative and immediate postoperative pain scores was compared with prospectively collected current pain on a Likert's scale (0–10). Additionally, patients were asked to complete a Short Form (SF)-20 and identify current pain medications. A two-sided Wilcoxon–Mann–Whitney test was used to analyze the data.Results Of the 30 patients identified, 16 could participate (mean follow-up = 61 months). The average pain reduction for the entire group was 62.7%. When using an established 30% reduction pain as a marker for clinical significance, 12 successful and 4 unsuccessful patients had an average reduction of 81.1 and 7.68%, respectively (success rate of 75%). Patients with successful group showed a statistically significant increased social functioning (p = 0.012) and near-significant increase in mental health (p = 0.063). Improvements, albeit nonsignificant, in mean scaled scores for every other SF-20 quality of life (QoL) category were observed when comparing both groups.Conclusion Neurectomy is a potentially beneficial surgery that can assuage pain and improve quality of life for patients with noniatrogenic groin neuralgia.
Keywords: noniatrogenic; groin neuralgia; neurectomy; quality of life